Incidence and risk factors for modic changes in the lumbar spine: a systematic review and meta-analysis - Cao, Zhenyu; Zhang, Mingtao; Jia, Jingwen; Zhang, Guangzhi; Li, Lei; Yang, Zhili; Zheng, Feng; Kang, Xuewen (Frontiers in Endocrinology, 2025)
BackgroundModic changes refer to bone marrow alterations beneath vertebral endplates and are potentially linked to infection, trauma, disc degeneration, scoliosis, and other pathological conditions. Systematic evaluations of their incidence and associated risk factors in the lumbar spine are lacking. This study aimed to analyze and evaluate the incidence and risk factors of Modic changes in lumbar spine disorders.MethodsA comprehensive systematic review was conducted using Web of Science, PubMed, Cochrane Library, and Embase databases. Eligible studies reported the incidence and associated risk factors of Modic changes in the lumbar spine. Data were extracted and systematically analyzed from the selected studies, and meta-analyses were conducted employing random or fixed effects models.ResultsTwenty-five studies were included in the meta-analysis. The overall incidence of Modic changes was 35%. Six risk factors were identified and quantitatively assessed. Strong evidence supported the association of endplate changes (OR=3.56; 95% CI=2.00 to 6.32; p<0.0001); moderate evidence supported the association of age (OR=4.01; 95% CI=1.37 to 6.65; p=0.003), disc degeneration (OR=8.54; 95% CI=1.98 to 36.73; p=0.004), and lumbar lordosis angle (OR=-4.14; 95% CI=-6.79 to -1.49; p=0.002); minor evidence supported the association of spondylolisthesis (OR=2.00; 95% CI=1.12 to 3.58; p=0.02) and physical labor (OR=1.81; 95% CI=1.08 to 3.04; p=0.03) with the occurrence of Modic changes in the lumbar spine. No significant associations were found to support body mass index, sex, disc herniation, smoking, distributional segmentation, or sacral slope angle as risk factors for Modic changes in the lumbar spine.ConclusionModic changes occur in 35% of lumbar spine cases, with advanced age, disc degeneration, endplate changes, spondylolisthesis, reduced anterior lumbar lordosis angles, and participation in physical labor identified as associated risk factors.